2021
DOI: 10.3390/jcm10050972
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Nicotine Addiction Prediction Models for Youth E-Cigarette and Waterpipe (Hookah) Users

Abstract: Despite the harmful effect on health, e-cigarette and hookah smoking in youth in the U.S. has increased. Developing tailored e-cigarette and hookah cessation programs for youth is imperative. The aim of this study was to identify predictor variables such as social, mental, and environmental determinants that cause nicotine addiction in youth e-cigarette or hookah users and build nicotine addiction prediction models using machine learning algorithms. A total of 6511 participants were identified as ever having u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…It is defined only by the number of trees and the depth of each tree. For a study using the random forest technique for addiction problems, please refer to [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is defined only by the number of trees and the depth of each tree. For a study using the random forest technique for addiction problems, please refer to [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Machine-learning has found steadily increasing applications in the addiction literature. Supervised ML methods have been used to predict adolescent alcohol use (102) and misuse (103), distinguish between smokers and non-smokers (104)(105)(106), between people with and without cocaine use disorder (107,108) or cannabis use disorder (109)(110)(111), and between people with different types of SUD (107,(112)(113)(114)(115)(116). These ML studies have identified multivariate neurobiological, neurocognitive, psychiatric, and personality profiles that differentiate addictions to different classes of drugs.…”
Section: Data-driven Approaches / Machine Learningmentioning
confidence: 99%
“…Therefore, our ML analysis can identify the important predictors that may be focused on for targeted polices and prevention programs. ML has been used in ENDS research ( Choi et al, 2021 , Fu et al, 2021 , Han et al, 2021 ), including in young adults ( Atuegwu et al, 2020 ). The goal in this study was to use ML to create predictive models and identify multiple prospective predictors of ENDS initiation in tobacco-naive young adults.…”
Section: Introductionmentioning
confidence: 99%